1978
DOI: 10.1177/1077727x7800700206
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Qualities, Cooking Losses, Shear Values, and B‐Vitamins of Beef Roasts Cooked by Slow‐Heat

Abstract: Top rounds of beef were cooked to internal temperature of 88°C in a portable oven‐broiler with a slow‐heat setting. Control roasts were cooked in a household electric oven (135°C). Total cooking losses were higher for roasts cooked by the slow‐heat oven‐broiler method than for the control roasts. Shear values and mean tenderness scores indicated that the meat cooked by the slow‐heat oven‐ broiler method was more tender than that cooked by the control method. There were no significant differences between mean f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Evidently, the roasting of the beef roasts four to five times longer at 80° C permitted a final "well-done" internal temperature of 70° C as opposed to that of 80° C required when roasted in a 125° C oven. 194 The magnitude of difference in rare beef roasts was only 4 to 5° C. Comparison of the roasting time of beef roasts (Table 8) prepared at the slow-heat setting of a Toastmaster Oven-Broiler® to a household electric oven indicated that the lower heating oven-broiler took approximately 60% longer cooking time. This is expected since the ambient temperature in the oven-broiler was at no time higher than 135° C. For most of the roasting period, it ranged from 70 to 105° C.…”
Section: Cooking Temperature and Methodsmentioning
confidence: 98%
“…Evidently, the roasting of the beef roasts four to five times longer at 80° C permitted a final "well-done" internal temperature of 70° C as opposed to that of 80° C required when roasted in a 125° C oven. 194 The magnitude of difference in rare beef roasts was only 4 to 5° C. Comparison of the roasting time of beef roasts (Table 8) prepared at the slow-heat setting of a Toastmaster Oven-Broiler® to a household electric oven indicated that the lower heating oven-broiler took approximately 60% longer cooking time. This is expected since the ambient temperature in the oven-broiler was at no time higher than 135° C. For most of the roasting period, it ranged from 70 to 105° C.…”
Section: Cooking Temperature and Methodsmentioning
confidence: 98%
“…SEM makes it possible to note the location of cracks and breaks as well as the fragmentation of muscle fibers that occur during heating of meat (Hearne, Penfield, and Goertz, 1978). This information is useful in explaining why slo* methods of heating promote tenderness (Bayne, Allen, Large, Meyer, and Goertz, 1973;Korschgen and Baldwin, 1978). Davis, Gordon, and Hutchison (1976a) evaluated methods of preparing carrot samples for SEM.…”
Section: The Methodological Domainmentioning
confidence: 99%